Genome-Wide Identification of Long Noncoding RNAs and Their Responses to Salt Stress in Two Closely Related Poplars - Ma, Jianchao; Bai, Xiaotao; Luo, Wenchun; Feng, Yannan; Shao, Xuemin; Bai, Qiuxian; Sun, Shujiao; Long, Qiming; Wan, Dongshi (Frontiers in Genetics, 2019)
Long non-coding RNAs (lncRNAs) are involved in various biological regulatory processes, but their roles in plants resistance to salt stress remain largely unknown. To systematically explore the characteristics of lncRNAs and their roles in plant salt responses, we conducted strand-specific RNA-sequencing of four tissue types with salt treatments in two closely related poplars (Populus euphratica and P. alba var. pyramidalis), and a total of 10,646 and 10,531 lncRNAs were identified, respectively. These lncRNAs showed significantly lower values in terms of length, expression and expression correction than with mRNA. We further found about 40% and 60% of these identified lncRNAs responded to salt stress with tissue-specific expression patterns across the two poplars. Furthermore, lncRNAs showed weak evolutionary conservation in sequences and exhibited diverse regulatory styles; in particular, tissue- and species-specific responses to salt stress varied greatly in two poplars, for example, 322 lncRNAs were found highly expressed in P. euphratica but not in P. alba var. pyramidalis and 3,425 lncRNAs were identified to be species-specific in P. euphratica in response to salt stress. Moreover, some conserved elements related to plant growth were identified in lncRNAs with predicted target genes included Aux/IAA, NAC, MYB, involved in regulating plant growth and the plant stress response. Taken together, the systematic analysis of lncRNAs between sister species enhance our understanding of the characteristics of lncRNAs and their roles in plant growth and salt response.